Fetal Sex Determination Using Cell-Free Fetal Dna (cffDNA) in Maternal Blood - Sanjaya, I Nyoman Hariyasa; Suwardewa, Tjok Gde Agung; Arijana, I G. Kamasan N. (BALI MEDICAL JOURNAL, 2016)
Background: Prenatal test has routinely performed in antenatal care and has become a part of the obstetric care feature in many countries. Prenatal test is divided into screening and diagnostic test. Recently, the early noninvasive method in order to found and lessen the risk factors of pregnancy loss, has been studied. One of the methods is molecular test using cffDNA which has many screening purpose such as sex determination, aneuploidy, paternal inherited genetic disorder, fetus rhesus, and performed early at 7 weeks of pregnancy. Objective: The purpose of this study is to measure diagnostic value of cffDNA in determining fetal sex prenatally. Methods: In a diagnostic test study, 18 randomized samples were selected and divided based on fetal gender confirmed at birth. The group consisted of 9 pregnant women with male babies and 9 pregnant women with female babies. CffDNA then isolated from maternal blood sample and specific region in Y chromosome termed SRY is detected by PCR and electrophoresis. The data obtained analyzed both descriptively for baseline characteristic and analytically to determine its diagnostic value. Results: This study found significant correlation between SRY detection in cffDNA with male fetal phenotype (p<0.05). The sensitivity of the method is 100% with 89% specificity. In addition, we found 9.09 values for positive likelihood ratio (LR+) and 0 for negative likelihood ratio (LR-). Moreover, the result yielded 100% positive predictive value (PPV+) and 88.8% of negative predictive value (PPV-). Conclusion: This study proofed that cffDNA have a great diagnostic value to determine fetal sex prenatally. However, further study with several group of gestational age mother and better matching is required to further confirm the diagnostic potential of cffDNA.